Osteoblasts engulf apoptotic bodies during alveolar bone formation in the rat maxilla - Cerri, Paulo Sérgio [UNESP] (Wiley-Blackwell, 2005)
During bone formation, as in other tissues and organs, intense cellular proliferation and differentiation are usually observed. It has been described that programmed cell death, i.e., apoptosis, takes place in the control of the cellular population by removing of the excessive and damaged cells. Although it is generally accepted that apoptotic bodies are engulfed by professional phagocytes, the neighboring cells can also take part in the removal of apoptotic bodies. In the present study, regions of initial alveolar bone formation of rat molars were examined with the aim to verify whether osteoblasts are capable of engulfing apoptotic bodies, such as professional phagocytes. Rats aged 11-19 days were sacrificed and the maxillary fragments containing the first molar were removed and immersed in the fixative solution. The specimens fixed in glutaraldehyde-formaldehyde were processed for light microscopy and transmission electron microscopy. For the detection of apoptosis, the specimens were fixed in formaldehyde, embedded in paraffin, and submitted to the TUNEL method. The results revealed round/ovoid structures containing dense bodies on the bone surface in close contact to osteoblasts and in conspicuous osteoblast vacuoles. These round/ovoid structures showed also positivity to the TUNEL method, indicating that bone cells on the bone surface are undergoing apoptosis. Ultrathin sections showed images of apoptotic bodies being engulfed by osteoblasts. Occasionally, the osteoblasts exhibited large vacuoles containing blocks of condensed chromatin and remnants of organelles. Thus, these images suggest that osteoblasts are able to engulf and degrade apoptotic bodies. (c) 2005 Wiley-Liss, Inc.
Keywords: osteoblasts; apoptosis; alveolar bone; bone cells; bone formation